Characterization Of Physicochemical Properties Of Passion Fruit (Passiflora Edulis) Effervescent Powder - Rizka Hasmi; Mayang Sari; Hendri Faisal; Wanda Hijriyani (Jurnal Kesmas Prima Indonesia, 2026)
The health drink market has evolved significantly, driving the development of innovative dosage forms like effervescent powders. Purple passion fruit (Passionflowerwas.edible) is a natural ingredient rich in bioactive antioxidants, including carotenoids, anthocyanins, flavonoids, and vitamin C. This study aims to formulate an effervescent powder utilizing purple passion fruit juice as an alternative health drink. An experimental laboratory design was employed to evaluate various physical properties and consumer acceptance. Passion fruit pulp was purposely sampled from Gajah Village, Karo Regency. The formulated effervescent granules were evaluated for organoleptic properties, foam height, dissolution time, pH levels, and hedonic preference using 12 semi-trained panelists. The results indicated that passion fruit juice can be successfully transformed into a stable effervescent powder. The preparation met all standard requirements for quality effervescent powders, showing an acceptable pH, rapid dissolution time, adequate foam height, and high acceptability in hedonic testing. In conclusion, the combination of citric acid, tartaric acid, and sodium bicarbonate yields an optimal effervescence reaction. Future studies should focus on long-term stability testing and developing this formulation into a compressed effervescent tablet.